Celiac disease and obstetrical-gynecological contribution - Casella, Giovanni (Gastroenterol Hepatol Bed Bench, 2016)
Celiac disease (CD) shows an increased prevalence in female, particularly during the fertile period. Celiac disease should be researched in infertility, spontaneous and recurrent abortions, delayed menarche, amenorrhea, early menopause, and children with low birth-weight. Celiac disease is still little considered during the evaluation of infertility. Up to 50% of women with untreated CD refer an experience of miscarriage or an unfavorable outcome of pregnancy. Celiac patients taking a normal diet (with gluten) have a shorter reproductive period. Women with undiagnosed CD had a higher risk of small for gestation age infants very small for gestational age infants and pre-term birth when compared with women with noted CD. The link between NCGS and infertility is actually unknown. The goal of our work is to perform an actual review about this topic and to increase the awareness in the medical population to research celiac disease in selected obstetric and gynecological disorders.